2020
DOI: 10.1186/s13148-020-00972-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered immune phenotype and DNA methylation in panic disorder

Abstract: Background Multiple studies have related psychiatric disorders and immune alterations. Panic disorder (PD) has been linked with changes in leukocytes distributions in several small studies using different methods for immune characterization. Additionally, alterations in the methylation of repetitive DNA elements, such as LINE-1, have been associated with mental disorders. Here, we use peripheral blood DNA methylation data from two studies and an updated DNA methylation deconvolution library to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
6
0
1
Order By: Relevance
“…While some findings in regard to platelet reactivity indicators and red cell distribution width in PD compared to healthy controls suggest their diagnostic and predictive capacity [ 33 , 34 ], investigations of immune markers in PD are still at the early stage. Petersen et al analyzed immune cell proportions from two previous case-control DNAm studies in PD and observed significantly lower proportions of CD8 + T-lymphocytes, higher proportion of neutrophil as well as increased neutrophil-to-lymphocyte ratio in PD cases, however, after adjustment for age and sex, only CD8 + reduction was still significant [ 17 ]. The authors suggest that reduced CD8 + T cells are consistent with lower levels of IFN-gamma previously detected in a case-control study in PD [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some findings in regard to platelet reactivity indicators and red cell distribution width in PD compared to healthy controls suggest their diagnostic and predictive capacity [ 33 , 34 ], investigations of immune markers in PD are still at the early stage. Petersen et al analyzed immune cell proportions from two previous case-control DNAm studies in PD and observed significantly lower proportions of CD8 + T-lymphocytes, higher proportion of neutrophil as well as increased neutrophil-to-lymphocyte ratio in PD cases, however, after adjustment for age and sex, only CD8 + reduction was still significant [ 17 ]. The authors suggest that reduced CD8 + T cells are consistent with lower levels of IFN-gamma previously detected in a case-control study in PD [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few case-control epigenome-wide association studies (EWAS) are available for PD or PD-related symptomatology showing significant association of CpG sites in genes involved in cell-cycle regulation and immune system with overall small effect sizes [14][15][16]. A meta-analysis of two published EWAS [17] identified 61 significantly differentially methylated CpGs on epigenomewide level. Several of those CpGs were annotated to genes which play a role in immune system regulations, such as the Tlymphokine-activated killer cell-originated protein kinase (TOPK) or in brain development and stress-induced depressive behavior, such as SMARCA5.…”
Section: Introductionmentioning
confidence: 99%
“…Petersen et al [29] investigated the leukocyte proportions and the methylation status of repetitive elements in PD patients. Authors found LINE-1 hypomethylation for PD cases in comparison to the control group (difference in mean beta value = 0.002, p < 0.001), remaining statistically significant after adjustments for sex, age, and years of study.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“… 1 2 The prevalence and clinical significance of this finding are not well established, but hypophosphatemia poses risk for numerous medical complications including myopathies resulting in dysphagia, cardiac dysfunction and respiratory failure, as well as seizures and coma. There are reports of acute complications from panic-related hypophosphatemia including lactate elevation 3 and episodic weakness, 4 as well as immune-mediated signalling associated with panic disorder, 5 6 but panic-related rhabdomyolysis has not been reported. This case demonstrates an uncommon instance of rhabdomyolysis deemed secondary to metabolic derangements during an acute panic attack.…”
Section: Introductionmentioning
confidence: 99%